ANALISIS FAKTOR- FAKTOR YANG BERPENGARUH TERHADAP PERMINTAAN TELUR AYAM RAS: STUDI KASUS: PERUSAHAAN ADAM FARM MAGETAN - Subhan Effendi; Nismawarni Nismawarni; Ilham Ahmad (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Changes in people's lifestyles that are increasingly concerned with health and nutrition for animal protein will be able to increase the demand for purebred chicken eggs. Demand for purebred chicken eggs at certain times will increase such as Eid al-Fitr or other holidays and demand will decrease on ordinary days. The purpose of this study was to determine what factors affect the demand for purebred chicken eggs at Adam Farm Company. This research was conducted in November 2023 at Adam Farm Company located in Kiringan Village, Magetan Regency, East Java. The data collection techniques used in this research are surveys, interviews, documentation, and questionnaires. The data analysis technique used in this study is quantitative using multiple linear regression tests. The results showed that partially the factors of broiler egg price, egg quality, number of dependents had a significant influence on the demand for broiler eggs, while the price of tempeh had no significant effect on the demand for broiler eggs. But simultaneously that the price of purebred chicken eggs, egg quality, number of dependents and the price of tempeh have a significant effect on the demand for purebred chicken eggs because the significant value obtained is 0.000 <0.05. So these factors together have a positive influence on the demand for purebred chicken eggs at Adam Farm Company in Magetan, East Java. The influence given by all these factors is 55.3% on the demand for purebred chicken eggs. While 48.2% is influenced by other factors outside this study.